Informática educativa : elementos para uma proposta de formação continuada de professores - Machado, Lisandro Lemos (2011)
Information technologies (ICTs) are increasingly becoming integrated in society in recent decades. Thus, the older generations have faced the constant need to adapt to use them, in everyday activities. In their turn, children and young in their majority already had contact with the ICTs since very early in life, growing up with its presence completely integrated to their reality. This generation gap reflects on school context, since students bring with them their experiences and worldview, arising out a society that provides many forms of interactive activities, however, many times they face very few or even none use of technological resources already present in school, thus because the lack of teachers adaptation to adequate utilization and exploration of the ITCs resources in their teaching practice. The central objective of this research is to characterize the teacher as the major subject in teaching-learning process modernization, conducting an analysis of government measures already taken to qualify them, as well as aspects related to the training received to work with the use of computers on education. To do this, beyond the theoretical research, - addressing how technologies affect the educational elements, accordance with Veen and Vraking, among others, detach, as well as the characteristics of them should be considered in the teaching process, conforming the concepts of connectivity of Siemens and cyberspace of Lévy, beyond the study of work done by researchers in this area as Guareschi, Siveris and Marcon - were performed the analysis of structures of the teaching degree courses curriculum at Universidade de Passo Fundo university, checking for disciplines that address the educational computing, as well as interviewing the chosen targeted public, in other words, former from Núcleo de Tecnologia Educacional (NTE) at Universidade de Passo Fundo and Prefeitura Municipal (the city hall), as well with students from degree courses and their teachers on diverse moments of their professional career. Based on the analysis was possible to determine the need to reform the way that university formation of teachers occurs, as well as raise aspects needed to be addressed in a methodology of a course in continuing education of teachers, in the sense of the integration of technology into the conventional school, providing continuous renewal and modernization of the same